Study on the Proportion of Orange Peel and Orange Juice with Sugar Addition on the Physicochemical and Organoleptic Characteristics of Siam Orange Jam - Mazaya El-Maula, Ghitsna; Rosida, Rosida; Dedin Finatsiyatul Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Siam oranges (Citrus nobilis) are abundant commodities, with the fruit flesh being commonly utilized, while the peel is often discarded as waste. The peel contains flavonoids, limonin, hesperidin, and pectin, which function as antioxidants and natural gelling agents. This study used both the peel and juice of Siam oranges, with the addition of sugar. The orange juice serves as a solvent for the mixture of ingredients, while sugar adds sweetness and helps maintain the consistency of the jam during cooking. The aim of this study was to investigate the effects of different proportions of orange peel and juice, with varying sugar concentrations, on the physicochemical and organoleptic characteristics of Siam orange jam, and to determine the optimal formulation. The experiment was designed using a Randomized Complete Block Design in a factorial pattern with two replications. Factor 1 consisted of the proportion of orange peel to orange juice (10:90, 20:80, 30:70), and Factor 2 involved sugar concentration (60%, 65%, 70%) with two replications. Data were analyzed using ANOVA and Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the best treatment was the 30:70 ratio of Siam orange peel to juice with 65% sugar (A3G2), which produced jam with the following characteristics: moisture content of 36.99%; pH of 3.44; total dissolved solids (TDS) of 64.24°Brix; reducing sugar of 20.32%; vitamin C content of 16.48 mg/100g; antioxidant activity of 52.10%; spreadability of 7.12 cm; crude fiber of 0.71%; and hedonic test scores for texture (3.16, slightly like), taste (3.12, slightly like), color (4.16, like), aroma (3.40, slightly like), and overall (3.24, slightly like). Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 8 : Decent Work and Economic GrowthSDG 9 : Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action